Mapping the CMB sky: The BOOMERanG experiment - DE BERNARDIS, Paolo; P. A. R. Ade; R. Artusa; J. J. Bock; A. Boscaleri; B. P. Crill; DE TROIA, Grazia; P. C. Farese; M. Giacometti; V. V. Hristov; IACOANGELI, Armando; A. E. Lange; et al. (New Astronomy Reviews, 1999)
1999NewAR.43.289D We describe the BOOMERanG experiment, a stratospheric balloon telescope intended to measure the Cosmic Microwave Background anisotropy at angular scales between a few degrees and ten arcminutes. The experiment has been optimized for a long duration (7 to 14 days) flight circumnavigating Antarctica at the end of 1998. A test flight was performed on 30 August 1997 in Texas. The level of performance achieved in the test flight was satisfactory and compatible with the requirements for the long duration flight.